Dabigatran Induced Hemorrhagic Cystitis in a Patient with Painful Bladder Syndrome. (13th March 2014) - Otteno, Helen; Smith, Erica; Huffaker, R. Keith
Abstract : An 82-year-old female presented with longstanding history of both painful bladder syndrome and atrial fibrillation. She underwent hydrodistension remarkable for hematuria without temporary discontinuation of Dabigatran. Subsequently, patient was admitted to the hospital secondary to anemia and hemorrhagic cystitis.